Epidemiological Study of Child Casualties of Landmines and Unexploded Ordnances: A National Study from Iran. Issue 5 (16th September 2015) - Mousavi, Batool; Soroush, Mohammad Reza; Masoumi, Mehdi; Khateri, Shahriar; Modirian, Ehsan; Shokoohi, Hamid; Fatemi, Mohammad Javad; Ali Hematti, Mohammad; Soroush, Mansour; Ghassemi-Broumand, Mohammad; Rassafiani, Mehdi; Allami, Mostafa; et al.
Abstract: Background: Despite landmine-risk education programs and extensive demining activities on the Western border of Iran, landmines and unexploded ordnance (UXOs) still cause civilian and child casualties three decades after the Iraq-Iran war (1980-1988). The objective of this study was to understand the epidemiological patterns and risk factors of injury in child casualties of landmines and UXOs in Western and Southwestern Iran. Methods: Children who were 18 years old or younger at the time of study and who sustained injuries from landmines and UXOs were identified through a search at the Iranian National Veterans Registry. These children participated in a 5-day gathering. The information on socioeconomic status, health-related issues, quality of life, health care utilization, and clinical profiles concerning the landmine and UXO injuries were collected. The method of data collection consisted of three component surveys: health interview, social survey, and medical examinations. Social surveys and health interviews were conducted in a face-to-face method by utilizing a questionnaire consisting of 39 questions addressing household and individual components, including information on time and type of injuries, physical activity, mental health, and quality of life. A comprehensive team of physicians in different subspecialties evaluated and examined children to assess the current medical and psychiatric conditions and physical activity, and recommended and arranged further medical, rehabilitation, or surgical planning. Results: Seventy-eight child casualties were identified and participated in the study. The mean age of the participants at the time of study was 16.11 years old (SD=2 years). The mean age of victims at the time of injury was 8.2 years (SD=3.12 years; ranged from 2 to 15 years old). Sixty-seven (85.9%) of the children were male. Provinces of Kurdistan and Kermanshah had the highest number of casualties, with a total number of 54 children (68.3%). Eighty percent of the injuries were caused by landmines, and UXO explosions were reported in 20% of the cases. Overall, 24 children (30%) had received some landmine-risk education before or after the events. Sixty percent of the explosions had happened in the morning between 9:00am and 12:00pm . Playing and grazing livestock were the most prevalent activities/reasons at the time of injury, which were reported in 77% of the subjects. Sixty-three percent of incidents had multiple casualties and in only 13 explosions were the children the only victims of the explosion. The most prevalent injuries were amputations in 41 subjects (52.56%), followed by hearing loss in 23 subjects (29.5%). Amputations were more common in upper extremities (62%) than in lower extremities (38%). Conclusion: Landmines and UXOs comprise a significant safety hazard to the children living in the Western border of Iran decades after the Iraq-Iran War. The large number of injuries and lack of risk training among victims suggest that landmine cleanings and landmine-risk education should be age-specifically targeted and expanded substantially. B Mousavi, MR Soroush, M Masoumi, S Khateri, E Modirian, H Shokoohi, MJ Fatemi, MA Hematti, M Soroush, M Ghassemi-Broumand, M Rassafiani, M Allami, F Nouri, A Yavari, Z Ganjparvar, M Kamyab, SA Mirsadeghi, Epidemiological study of child casualties of landmines and unexploded ordnances: a national study from Iran .Prehosp Disaster Med .2015 ;30 (5 ):472 –477 .